2000
DOI: 10.1007/s002530000478
|View full text |Cite
|
Sign up to set email alerts
|

Liquid media development for Heterorhabditis bacteriophora : lipid source and concentration

Abstract: Lipids are important entomopathogenic nematode nutritional components because they are energy reserves and serve as indicators of nematode quality. The composition and concentration of the media lipid component determine bacterial and nematode yields. Heterorhabditis bacteriophora and its symbiont, Photorhabdus luminescens, were cultured in media containing various lipid sources. As lipid concentration increased from 2.5% to 8.0% (w/v), the final yield and productivity [calculated from the number of infective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 0 publications
0
30
0
3
Order By: Relevance
“…However, use of first stage juveniles in commercial mass production may be problematic relative to using IJs. Inoculum based on IJs has been successfully used for commercial production because high concentrations of IJs can be easily obtained and stored, increasing nematode yields and advancing harvest in 2 wk post inoculation (Strauch and Ehlers, 1998;Jeffke et al, 2000;Yoo et al, 2000;Hirao and Ehlers, 2009;Shapiro-Ilan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, use of first stage juveniles in commercial mass production may be problematic relative to using IJs. Inoculum based on IJs has been successfully used for commercial production because high concentrations of IJs can be easily obtained and stored, increasing nematode yields and advancing harvest in 2 wk post inoculation (Strauch and Ehlers, 1998;Jeffke et al, 2000;Yoo et al, 2000;Hirao and Ehlers, 2009;Shapiro-Ilan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It also forms, food reserves of juveniles, as well as, the body wall of juveniles and adult forms (J 1 , J 2 , and J 3 , male and female). Yoo et al (2000) reported that lipids are important entomopathogenic nematode nutritional components as they are energy reserves and serve as indicators of nematode quality. The results of the present study indicate that adult females of both the species have higher concentration of lipids than their juveniles, but the concentration of lipids in the two different species of Meloidogyne i.e., M. javanica and M. incognita do not show considerable differences.…”
Section: Resultsmentioning
confidence: 99%
“…Inkonsistensi tingkat produksi JI pada media in vitro disebabkan oleh laju pemulihan (recovery) inokulum JI yang rendah dan tidak sinkron ke tahap perkembangan stadia selanjutnya (Yoo et al, 2000). Di dalam tubuh serangga inang, tingkat pemulihan JI sebesar 95% dapat terjadi serempak dalam satu hari, sedangkan pada media in vitro pemulihan tersebar dalam beberapa hari dengan tingkat yang bervariasi, antara 0-81% (Strauch dan Ehlers, 1998dalam Yoo et al, 2000.…”
Section: Potensi Reproduksi Jiunclassified